2021
DOI: 10.3390/ijms22030993
|View full text |Cite
|
Sign up to set email alerts
|

Little Helpers or Mean Rogue—Role of Microglia in Animal Models of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is one of the most common neurodegenerative diseases, causing degeneration of both upper and lower motor neurons in the central nervous system (CNS). ALS patients suffer from hyperreflexia, spasticity, paralysis and muscle atrophy and typically die due to respiratory failure 1–5 years after disease onset. In addition to the degeneration of motor neurons on the cellular level, ALS has been associated with neuroinflammation, such as microgliosis. Microglial activation in ALS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 109 publications
(209 reference statements)
0
4
0
Order By: Relevance
“…Various mouse models with different ALS-associated mutations are currently available to study the pathomechanisms of ALS (Stephenson and Amor, 2017 ; Cihankaya et al, 2021 ), including the Wobbler mouse, which was first described by Falconer in 1956 (Andrews et al, 1974 ; Giorgio et al, 2019 ). The Wobbler mouse displays almost the same symptoms as human ALS patients at the clinical-symptomatic, cellular and metabolic levels (Boillée et al, 2003 ; Moser et al, 2013 ; Ott et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various mouse models with different ALS-associated mutations are currently available to study the pathomechanisms of ALS (Stephenson and Amor, 2017 ; Cihankaya et al, 2021 ), including the Wobbler mouse, which was first described by Falconer in 1956 (Andrews et al, 1974 ; Giorgio et al, 2019 ). The Wobbler mouse displays almost the same symptoms as human ALS patients at the clinical-symptomatic, cellular and metabolic levels (Boillée et al, 2003 ; Moser et al, 2013 ; Ott et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary objectives of this study was to determine whether disruption of scat expression in adult flies caused phenotypes like those observed in the wobbler mouse. While mutations in Vps54 have not been directly linked to human disease, the wobbler mouse has been used by many researchers as a model for the sporadic form of ALS because of striking similarities to ALS pathology ( Ikeda et al, 1998 ; Dennis and Citron, 2009 ; Nieto-Gonzalez et al, 2011 ; Moser et al, 2013 ; Dahlke et al, 2015 ; Schmitt-John, 2015 ; Klatt et al, 2019 ; Rohm et al, 2019 ; Cihankaya et al, 2021 ; De Nicola et al, 2021 ). It has previously been shown that scat mutants share spermatogenesis defects caused by Golgi dysfunction with the wobbler mouse ( Castrillon et al, 1993 ; Fari et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Motor neuron degeneration is generally accompanied by neuroinflammation in both ALS patients [ 7 , 8 ] and in the animal models of ALS [ 9 ]. Neuroinflammation is the natural response of the innate immune system in the central nervous system (CNS), and when left uncontrolled, chronic inflammation starts to pose a danger to motor neurons, causing premature cell death.…”
Section: Introductionmentioning
confidence: 99%